Gambaran Karakteristik Pasien Retinopati Hipertensi di Poli Mata RSUD H. Abdul Manap Kota Jambi Periode Tahun 2015-2021 - Sari, Wintan; Riasari, Vonna; Mulyadi, Deri (Journal of Medical Studies, 2023)
ABSTRACT Background: Hypertensive retinopathy is a condition with changes in retinal vascularity in a population suffering from hypertension and one of the earliest target organ damage in hypertension, so the condition of the retinal blood vessels is often used as a measure of the condition of the blood vessels of other organs of the body. The purpose of this study was to determine the characteristics of hypertensive retinopathy patients at RSUD H. Abdul Manap kota jambi. Methods: This research uses a descriptive observational method with a cross-sectional research design. The sample for this study was medical record data of hypertensive retinopathy patients at the eye clinic at RSUD H. Abdul Manap Kota Jambi. The variables in this study were age, sex, degree of hypertension, length of time suffering from hypertension, and body mass index. The total number of samples is 32 people. Results: Based on age, the highest category was found at the age of 51-50 years, with 15 people (46.%). Based on gender sex, the most categories were men, namely 20 people (62.5%). Based on the degree of hypertension, the highest category was grade 1 hypertension, namely 19 people (59.4%). Based on the duration of suffering from hypertension, the highest category was found in the <5 years group, namely 19 people (59.4%). Based on body mass index, the highest category was found in the obesity group 1, namely 14 people (43.8%). Conclusion: Most characteristics of hypertensive retinopathy patients based on age were 51-50 years old, based on sex the most were male, based on the degree of hypertension the most were grade 1 hypertension, based on the duration of suffering from hypertension the most is <5 years, based on the highest body mass index is obesity 1. Key words: Hypertensive retinopathy, Patient characteristics ABSTRAK Latar Belakang: Retinopati hipertensi merupakan suatu kondisi dengan perubahan vaskularisasi retina pada populasi yang menderita hipertensi dan salah satu kerusakan organ target paling awal pada hipertensi, sehingga keadaan pembuluh darah retina sering dipakai sebagai ukuran keadaan pembuluh darah organ tubuh lain. Tujuan penelitian ini adalah untuk mengetahui karakteristik pasien retinopati hipertensi di RSUD H. Apdul Manap. Metode: Peneitian ini menggunakan metode deskriptif observasional dengan desain penelitian cross-sectional. Sampel peneitian ini adalah data rekam medis pasien retinopati hipertensi di poli mata RSUD H. Abdul Manap Kota Jambi. Variabel peneitian ini adalah usia, jenis kelamin, derajat hipertensi, lamanya menderita hipertensi, dan indek masa tubuh. Jumlah total sampel adalah 32 orang. Hasil: Berdasarkan usia di dapatkan kategori terbanyak pada umur 51 – 50 tahun sebanyak 15 orang (46,%). Berdasarkan jenis kelamin di dapatkan kategori terbanyak adalah laki-laki yaitu sebanyak 20 orang (62,5%). Berdasarkan derajat hipertensi di dapatkan kategori terbanyak adalah hipertensi derajat 1 yaitu sebanyak 19 orang (59,4%). Berdasarkan lamanya menderita hipertensi di dapatkan kategori terbanyak pada kelompok < 5 tahun yaitu sebanyak 19 orang (59,4%). Berdasarkan indek masa tubuh di dapatkan kategori terbanyak pada kelompok obesitas 1 yaitu sebanyak 14 orang (43,8%). Kesimpulan: Karakteristik pasien retinopati hipertensi terbanyak berdasarkan usia adalah umur 51- 50 tahun, berdasarkan jenis kelamin terbanyak adalah laki-laki, berdasarkan derajat hipertensi terbanyak adalah hipertensi derajat 1, berdasarkan lamanya menderita hipertensi terbanyak adalah <5 tahun, berdasarkan indeks masa tubuh terbanyak adalah obesitas 1. Kata Kunci: Retinopati hipertensi, Karakteristik pasien